DIOSMECTIT IN COMPLEX THERAPY OF ACUTE VIRAL AND BACTERIAL ENTERIC INFECTIONS IN CHILDREN - G.M. Filippova; I.V. Ivanov; O.E. Efimenko; S.M. Manchenko ("Paediatrician" Publishers LLC, 2008)
Clinical course of acute enteric infection (AEI) in patients from 6 months to 5 years was analyzed. addition of diosmectit (neosmectin) in suspension to the complex therapy of AEI in children (n = 70) reduced duration of intestinal syndrome and eliminated intoxication faster then in group of children, treated with only basic therapy (n = 55). Effectiveness of diosmectit was strongly pronounced in children upwards 1 year old and did not depend on period of its prescription (from the onset of disease). Confirmed laboratory effectiveness of diosmectit allows using it in treatment of patients with viral and bacterial AEI.Key words: children, acute enteric infection, diosmectit, treatment.